Dementia and the Advance Directive Lessons from the Bedside - Sokolowski, Marcia (Springer International Publishing, 2018)
This unique title offers a novel exploration into the world of advance directives for patients with dementia. Based on real life ethics consultations the expert author has undertaken, the cases depict fascinating and challenging moral issues arising in a variety of healthcare facilities. The dynamics of the interdisciplinary health care teams of these patients, along with the dynamics of the families who are grappling to best serve their loved ones, are outlined and assessed; and the role each player's personal histories have on the ethical issues and their resolution in real life are explored. Following each case study, the author applies a range of concepts introduced in the beginning of the book to the relevant case study, thus integrating theory with a case-based approach. A user-friendly question-and-answer format provides a thought provoking and accessible learning experience for readers. Dementia and the Advance Directive: Lessons from the Bedside tackles complicated and realistic healthcare scenarios and offers an invaluable addition to the literature on advance directives. .